2019
DOI: 10.1038/s41598-019-39436-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of a Piezo-like protein suppressing systemic movement of plant viruses in Arabidopsis thaliana

Abstract: As obligate intracellular phytopathogens, plant viruses must take advantage of hosts plasmodesmata and phloem vasculature for their local and long-distance transports to establish systemic infection in plants. In contrast to well-studied virus local transports, molecular mechanisms and related host genes governing virus systemic trafficking are far from being understood. Here, we performed a forward genetic screening to identify Arabidopsis thaliana mutants with enhanced susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…Genome‐wide screens of Saccharomyces cerevisiae (yeast) replicating brome mosaic virus (BMV) (Kushner et al , ) or tomato bushy stunt virus (TBSV) (Panavas et al , ) showed that a compatible host contains both pro‐viral and antiviral factors that affect virus replication at the cellular level. Mutagenesis and genetic analyses in Arabidopsis thaliana (Arabidopsis) allowed identification of pro‐viral and antiviral factors that affect virus replication at the cellular level, cell‐to‐cell and systemic movement (Diaz‐Pendon et al , ; Garcia‐Ruiz et al , ; Guo et al , ; Lellis et al , ; Zhang et al , ). Accordingly, viruses need pro‐viral host factors and are targeted by antiviral host factors.…”
Section: Host Determinants Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome‐wide screens of Saccharomyces cerevisiae (yeast) replicating brome mosaic virus (BMV) (Kushner et al , ) or tomato bushy stunt virus (TBSV) (Panavas et al , ) showed that a compatible host contains both pro‐viral and antiviral factors that affect virus replication at the cellular level. Mutagenesis and genetic analyses in Arabidopsis thaliana (Arabidopsis) allowed identification of pro‐viral and antiviral factors that affect virus replication at the cellular level, cell‐to‐cell and systemic movement (Diaz‐Pendon et al , ; Garcia‐Ruiz et al , ; Guo et al , ; Lellis et al , ; Zhang et al , ). Accordingly, viruses need pro‐viral host factors and are targeted by antiviral host factors.…”
Section: Host Determinants Of Infectionmentioning
confidence: 99%
“…Plants encode mechanosensitive ion channels that regulate ion movement across cells. In Arabidopsis, ESC1 encodes a piezo protein that functions as a mechanosensitive Ca 2+ permeable channel and limits systemic infection of CMV and TuMV (Zhang et al , ).…”
Section: Host Genes With Antiviral Activitymentioning
confidence: 99%
“…To construct Arabidopsis thaliana ccp mutant lines, two 19 bp sequences (see Supplementary Table S1 at JXB online) specifically targeting the 5' coding region of CCP were cloned into the pHEC401 vector as described previously ( Xing et al , 2014 ; Zhang et al , 2019 ). All primers used for plasmid constructions are listed in Supplementary Table S1 , and all the plasmids were verified by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial growth was assessed in three independent experiments. For virus infection assay, three fully grown leaves of 4-week-old Arabidopsis plants were mechanically inoculated with Cucumber mosaic virus (CMV; 20 ng μl –1 ) as described previously ( Zhang et al , 2019 ). Systemically infected leaves were collected for RNA analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Given that PIEZOs play prominent roles in multiple aspects of animal mechanosensation and physiology [16][17][18][19] , we investigated the role of AtPIEZO in plant mechanosensation. A recent study reported that AtPIEZO regulated virus translocation within the plant, but its specific role in mechanotransduction was not addressed 20 . Here we use genetic tools, electrophysiological methods and calcium imaging to investigate the role of AtPIEZO in root mechanosensation.…”
mentioning
confidence: 99%